2020
DOI: 10.1111/1365-2745.13331
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of genetic diversity and relatedness in tree seedling growth and mortality: A multispecies study in a Bornean rainforest

Abstract: 1. Where conspecific seedlings occur at high densities, density-dependent processes tend to depress their performance and survival relative to co-occurring heterospecifics. We extend this observation to within-species genetic diversity and relatedness. We posit that seedling growth and survival increase where there is higher genetic diversity, and lower relatedness, among seedling populations, under the expectation that increased genetic dissimilarity among conspecific seedlings affords greater resistance to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 91 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…This overall consistent low genetic diversity and high inbreeding in progeny compared to adults is likely to be a natural process in our study species, similar to other tree species with strong FSGS (Nakanishi et al., 2015). These patterns further indicate the potential of purging (Wu et al., 2016; Yang et al., 2018) or strong selective forces against inbred seedlings for germination, establishment (Finger et al., 2011), growth, and survival (Nutt et al., 2016; Tito de Morais et al., 2019), and in favor for outbred individuals (Ismail et al., 2014b). In our study, since seedlings were nursery germinated, they were not subject to potential the selective forces that would likely shape their patterns in germination success in natural conditions, favoring less inbred progeny.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This overall consistent low genetic diversity and high inbreeding in progeny compared to adults is likely to be a natural process in our study species, similar to other tree species with strong FSGS (Nakanishi et al., 2015). These patterns further indicate the potential of purging (Wu et al., 2016; Yang et al., 2018) or strong selective forces against inbred seedlings for germination, establishment (Finger et al., 2011), growth, and survival (Nutt et al., 2016; Tito de Morais et al., 2019), and in favor for outbred individuals (Ismail et al., 2014b). In our study, since seedlings were nursery germinated, they were not subject to potential the selective forces that would likely shape their patterns in germination success in natural conditions, favoring less inbred progeny.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the reproduction of populations in degraded sites may become increasingly limited, leading to reductions in effective population sizes. This in turn can undermine the genetic resource base of populations, leading to erosion of genetic diversity, with negative effects on seedling growth (Nakanishi et al., 2015; Shao et al., 2018) and mortality (Costa E Silva et al., 2011; Nutt et al., 2016; Tito de Morais et al., 2019). For adult trees, this can reduce productivity by compromising flowering (Engelhardt et al., 2014), lowering fruit set, and increasing fruit abortion (Jones & Comita, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A preferred reporting items for meta-analyses diagram ( Moher et al, 2009 ) of the literature screening process is shown in Figure 1—figure supplement 2 . In total our dataset consisted of 210 effect sizes from 75 studies and 56 species ( Abdi et al, 2020 ; Agashe, 2009 ; Aguirre and Marshall, 2012a ; Aguirre and Marshall, 2012b ; Altermatt and Ebert, 2008 ; Anton et al, 2007 ; Baer and Schmid-Hempel, 2001 ; Baer and Schmid-Hempel, 1999 ; Ben-Ami and Heller, 2005 ; Bensch and Cornwallis, 2017 ; Bichet et al, 2015 ; Byrne and Robert, 2000 ; Byrne and Whiting, 2011 ; Cook‐Patton et al, 2017 ; Cook-Patton et al, 2011 ; Crutsinger et al, 2006 ; Crutsinger et al, 2008 ; Dagan et al, 2017 ; Dagan et al, 2013 ; de Morais, 2020 ; Desai and Currie, 2015 ; de Vere et al, 2009 ; Dobelmann et al, 2017 ; Ellison et al, 2011 ; Field et al, 2007 ; Franklin et al, 2012 ; Fraser et al, 2010 ; Gamfeldt and Källström, 2007 ; Ganz and Ebert, 2010 ; Gardner et al, 2007 ; He and Lamont, 2010 ; Hoggard et al, 2013 ; Hughes and Stachowicz, 2004 ; Hughes and Boomsma, 2006 ; Hughes and Boomsma, 2004 ; Johansson et al, 2007 ; Johnson et al, 2006 ; Kapranas et al, 2016 ; Keeney et al, 2009 ; King et al, 2011 ; Kotowska et al, 2010 ; Lambin and Krebs, 1993 ; Liersch and Schmid-Hempel, 1998 ; Mattila et al, 2012 ; McLeod and Marshall, 2009 ; Mott et al, 2019 ; Neumann and Moritz, 2000 ; Page et al, 1995 ; ...…”
Section: Methodsmentioning
confidence: 99%
“…A preferred Reporting Items for Meta-Analyses diagram (PRISMA Moher et al, 2009) of the literature screening process is shown in figure S2). In total our dataset consisted of 210 effect sizes from 75 studies and 56 species ((Abdi et al, 2020;Agashe, 2009; J. David Aguirre and Marshall, 2012; J. D. Altermatt and Ebert, 2008;Anton et al, 2007;Baer and Schmid-Hempel, 2001;Baer and Schmid-Hempel, 1999;Ben-Ami and Heller, 2005;Bensch and Cornwallis, 2017;Bichet et al, 2015;Byrne and Robert, 2000;Phillip G. Byrne and Whiting, 2011b;Cook-Patton et al, 2017Crutsinger, 2006;Gregory M Crutsinger et al, 2008 ;Gregory M. Crutsinger et al, 2008;Dagan et al, 2017Dagan et al, , 2013de Morais et al, 2020;Desai and Currie, 2015;de Vere et al, 2009;Dobelmann et al, 2017;Ellison et al, 2011;Field et al, 2007;Franklin et al, 2012;Fraser et al, 2010;Gamfeldt and Källström, 2007;Ganz and Ebert, 2010;Gardner et al, 2007;He and Lamont, 2010;Hoggard et al, 2013;Hughes and Stachowicz, 2004;Boomsma, 2006, 2004;Johansson et al, 2007;Kapranas et al, 2016;Keeney et al, 2009;King et al, 2011;…”
Section: Literature Searchesmentioning
confidence: 99%